answersLogoWhite

0


Best Answer

You remember that 'sum' means addition so that's b+11

User Avatar

Wiki User

8y ago
This answer is:
User Avatar
More answers
User Avatar

Wiki User

8y ago

You can write "the sum of..." with a plus sign; in this case:b + 11.

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: The sum of b and 11?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is the sum of b and 11?

b+11


If two fair dice are rolled what is the probability of rolling a double given that the sum was 11?

Let A = rolling a double Let B = sum is 11 P(A)=6/36=1/6 P(B)=2/36=1/18 since (5,6) and (6,5) produce a sum of 11. We want to find P(A/B)= P(A & B) / P(B) = 0 / P(B)=0 P(A & B) represent the event getting a double and the sum being 11.


The sum of two numbers is 35 Their difference is 11 What are the two numbers?

a + b = 35 a - b = 11 2b + 11 = 35 2b = 24 b = 12 a = 23


What is the divisibility rule of 11?

Add together all the digits in the odd positions in the number. Sum = A Add together all the digits in the even positions in the number. Sum = B If A-B is 0 or if it divisible by 11 (positive or negative), then the original number is divisible by 11.


Put 12345 and 6 in circles below for sum 11 in figure A and B?

No, thanks.


What is the sum of 11 and 11?

The sum of 11 and 11 is 22.


Write a c program that multiplies two numbers by repeated subtraction?

int mul (int a, int b) { int sum= 0; for (; b>0; --b) sum -= -a; for (; b<0; ++b) sum -= a; return sum; }


The sum of addends 11 and 15 is?

The sum of addends 11 and 15 is: 11 + 15 = 26


What is the sum Of?

The sum of is the total of everything being summed; the sum total. Thus the sum of a, b and c is therefore a + b + c.


The sum of two numbers is 25 while their difference is 11. What are the two numbers?

If a + b = 25 and a - b = 11 as asked, we can solve like this: a - b = 11 => a = 11 + b [Now we have expressed a in terms of b. Let's substitute that information in the first equation.] a + b = 25 => (11 + b) + b = 25 => 11 + b + b = 25 => 11 + 2b = 25 => 2b = 14 => b = 14/2 & b = 7 Substitute the value for b (the 7) into either equation and solve like this: a + b = 25 => a + 7 = 25 => a = 25 - 7 & a = 18 Lastly, substitute your answers into either equation and see if it checks.


What adds up to -2 and multiplies to -10?

The answer is √11 - 1, and -1 - √11. Here is one method of finding it: Let a + b = -2, and ab = -10. Now, (a + b)2 = a2 + 2ab + b2, and (a - b)2 = a2 - 2ab + b2. Subtracting, we have (a + b)2 - (a - b)2 = 4ab = - 40, whence (a - b)2 = (a + b)2 + 40 = 4 + 40 = 44, and a - b = √44 = 2√11. Adding a + b = -2, and a - b = 2√11, we have, 2a = 2√11 - 2, giving a = √11 - 1, and b = -1 - √11. The sum of these is clearly -2, and their product is -10.


What is the sum of 88 and 11?

The sum of 88 and 11 is 99.